Cells are initially detected in frame t0 and then tracked to frame t1. Object queries are processed in the first layer of the decoder for object detection. In the subsequent decoder layers, track queries are concatenated with the object queries to perform tracking. - Owen M. O’Connor (11965460) (2025)
Cells are initially detected in frame t0 and then tracked to frame t1. Object queries are processed in the first layer of the decoder for object detection. In the subsequent decoder layers, track queries are concatenated with the object queries to perform tracking.